Enhancing irrigated forage crop production through water and nutrient management in the Ethiopian sub-humid highlands - Hussein, Misbah A.; Haileslassie, Amare; Derseh, Melkamu B.; Assefa, Tewodros T.; Riga, Fikadu T.; Adie, Aberra; Tebeje, Aschalew K.; Jones, Chris S.; Tilahun, Seifu A. (Frontiers in Sustainable Food Systems, 2024)
Introduction The increasing pressure on land and water resources, fueled by high population growth and climate change, has profound implications for crop yield and quality. While studies thrive for various crops, a notable research gap exists in understanding the responses of forage crops to irrigation and nutrient management in developing countries. This study aims to address this gap by assessing the impact of irrigation and fertilizer application on forage production in the Ethiopian sub-humid highlands. Methods The experiment focused on four forage varieties, namely Napier grass (Cenchrus purpureus) cultivars, ILRI-16791, ILRI-16819, ILRI-16803, and Guinea grass (Megathyrsus maximus) ILRI-144 cultivated in experimental plots. Three irrigation levels designated as IR60 (60% of total available soil water), IR80 (80%), and IR100 (100%) were applied, along with three fertilizer rates: organic manure at 30 t ha−1, and Urea-N at 100 kg ha−1 and 300 kg ha−1. Agronomic data including growth performance, forage dry matter yield, and nutritional quality were collected during two trial years. Results and discussion Among the various irrigation treatments, IR80 demonstrated the most favorable balance between forage yield, WUE, net benefit, and LWP. In addition, the highest DMY, WUE, net benefit, and LWP were obtained for UREA at the rate of 300 kg ha−1 while the lowest DMY and WUE were observed for UREA at the rate of 100 kg ha−1. Significant variations were observed among the four forage varieties, with Napier grass ILRI-16791 having the highest DMY (9.8 tons ha−1), WUE (39 kg ha−1 mm−1), LWP (0.28 USD m−3 for local cows, and 1.04 USD m−3 for crossbred cows), and net benefit (783 USD ha−1). For all forages combined, a 40 and 20% decrease in irrigation increased water use efficiency by 17 and 9.4%, respectively. These results indicate that a moderate level of deficient irrigation such as IR80 could be a viable water management strategy for irrigated forage, especially in water-scarce areas. The conserved water saved from the deficit irrigation can thus be used to irrigate additional land, contributing to a more sustainable and efficient water usage approach.